2023
DOI: 10.1002/admt.202301003
|View full text |Cite
|
Sign up to set email alerts
|

Wirelessly Actuated Ciliary Airway Stent for Excessive Mucus Transportation

Yusheng Wang,
Saksham Sharma,
Fabien Maldonado
et al.

Abstract: Small‐scale cilia‐like devices that can manipulate fluids in narrow spaces have great potential in microfluidics, biomechanics, biomedical engineering, and other applications. However, prior studies mostly focus on artificial cilia for pumping fluids in lab‐on‐a‐chip microfluidic applications. The design and control of artificial cilia for transporting viscous mucus in confined and tubular structures remain challenging and medical devices such as airway stents with ciliary function are still missing. Herein, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Further studies using a controlled magnetic field activation need to be performed to optimize the cilia motion conditions and generate an effective fluid flow [ 40 ]. Moreover, it was recently demonstrated that the presence of a hydrophilic lubricant layer within a ciliary array accelerates the transportation of viscous fluids, including porcine mucin, and thus, can be an interesting strategy to enhance mucociliary clearance in ciliated stents [ 41 ]. It is worth noting that the mucus deposition on the substrate can accelerate its dehydration and hinder its displacement through the coughing mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies using a controlled magnetic field activation need to be performed to optimize the cilia motion conditions and generate an effective fluid flow [ 40 ]. Moreover, it was recently demonstrated that the presence of a hydrophilic lubricant layer within a ciliary array accelerates the transportation of viscous fluids, including porcine mucin, and thus, can be an interesting strategy to enhance mucociliary clearance in ciliated stents [ 41 ]. It is worth noting that the mucus deposition on the substrate can accelerate its dehydration and hinder its displacement through the coughing mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…porcine mucin, and thus, can be an interesting strategy to enhance mucociliary clearance in ciliated stents [41]. It is worth noting that the mucus deposition on the substrate can accelerate its dehydration and hinder its displacement through the coughing mechanism.…”
Section: Rationale For the Magnetic Cilia And Qualitative Analysis Of...mentioning
confidence: 99%
“…Directional transport of biological molecules in interstitial fluid flow via pressure-driven or self-propelled motion is of critical importance for living organisms. Inspired by natural biomolecular motions, artificial cilia systems and biomolecular-motor-based systems have been developed to achieve micrometer- or nanoscale transport of biomolecules, offering promising applications in bioseparations, biosensing, and biomedical drug delivery. Specifically, the transport of biomolecules such as DNA and peptides in microfluidic/nanofluidic networks has attracted considerable attention in the novel lab-on-a-chip bioanalysis technology. Stein et al studied the pressure-driven mobility and dispersion of DNA molecules in microfluidic and nanofluidic channels, which reflected the statistical properties of DNA polymer coils. Menard and Ramsey investigated the dynamic nature of the electrophoretically driven transport of double-stranded DNA through focused ion beam milled nanochannels.…”
Section: Introductionmentioning
confidence: 99%